Comprehensive Complication Index Predicts Cancer-Specific Survival of Patients with Postoperative Complications after Curative Resection of Gastric Cancer - Ru-Hong Tu; Jian-Xian Lin; Ping Li; Jian-Wei Xie; Jia-Bin Wang; Jun Lu; Qi-Yue Chen; Long-long Cao; Mi Lin; Chao-Hui Zheng; Chang-Ming Huang (Gastroenterology Research and Practice)
Objective. To investigate the prognostic impact of postoperative complications for patients with gastric cancer. Methods. Postoperative complications of patients undergoing radical gastrectomy for gastric cancer were reviewed. The severity of complications was graded by the CCI and C-D classification. Results. A total of 5327 patients were included in the study. Complications were observed in 767 patients. When the C-D classification system was applied, for patients with grade I–II complications, the length of stay (LOS) of those with high CCI (CCI ≥ 26.2) was significantly longer than that of patients with low CCI (CCI < 26.2) (p<0.001). The 5-year cancer-specific survival rate of patients with complications (52%) was lower than that of patients without complications (61%) (p<0.001). Analysis of the factors associated with prognosis in patients with gastric cancer revealed that complications were independent risk factors for specific survival. When CCI was used to classify complication severity, the 5-year cancer-specific survival rate of the high-CCI group was 46.3%, which was lower than that of the low-CCI group (54.9%, p=0.009). Conclusion. Complication after radical gastrectomy is an independent prognostic factor, and the complication severity as graded by CCI reflects the difference of cancer-specific survival in gastric cancer patients with postoperative complications.